'A Part' of the World: Deleuze and the Logic of Creation. Issue 1 (February 2017) - Satoor, Christopher
Abstract : Is there a particular danger in following Deleuze's philosophy to its end result? According to Peter Hallward, Deleuze's philosophy has some rather severe conclusions. Deleuze has been portrayed by him as a theological and spiritual thinker of life. Hallward seeks to challenge the accepted view of Deleuze, showing that these accepted norms in Deleuzian scholarship should be challenged and that, initially, Deleuze calls for the evacuation of political action in order to remain firm in the realm of pure contemplation. This article intends to investigate and defend Deleuze's philosophy against the critical and theological accounts portrayed by Hallward, arguing that Deleuze's philosophy is not only creative and vital but also highly revolutionary and 'a part' of the given world. It then goes on to examine Hallward's distortion of the actual/virtual distinction in Deleuze because Hallward is not able to come to grips with the concept of life in Deleuze's philosophy. We live in an intensive and dynamic world and the main points of Deleuze's philosophy concern the transformation of the world. Deleuze is not seeking to escape the world, but rather to deal with inventive and creative methods to transform society.